On the converse problem for the Gross-Pitaevskii equations with a large parameter - Norman Dancer (Discrete and Continuous Dynamical Systems, 2013)
From External's report: This is a high quality work by an internationally leading researcher in the field. The proofs rely on known techniques and the author manages to make them look relatively easy. I think there are not many people in the world who can navigate these waters with the same ease as the author, so the proofs are actually more difficult than they might appear.